387 Minimally Invasive TTC Arthrodesis - Novel Arthroscopic Assisted Hindfoot Nailing. (19th August 2022) - Lingnau, L; Morris, R; Cheruvu, MS; Mumtaz, H
Abstract: Aim: Tibiotalocalcaneal arthrodesis is a salvage procedure for advanced primary degenerative joint disease of the hindfoot and ankle, failed primary fixation, post-traumatic osteoarthritis, or Charcot disease. Hindfoot nailing has been associated with complications in up to 40% of cases. There is limited literature on arthroscopic arthrodesis, as an advanced and minimally invasive technique. Our aim is to evaluate this pioneering minimally invasive procedure in terms of radiological and operative outcomes. Method: We conducted a retrospective analysis of all patients who underwent this procedure at a single centre by a specialist foot and ankle service. We noted procedure indication, post-operative complications, and post-operative outcome in all patients. Outcomes include wound defects or infection, radiographic evidence of fusion, fixation failure, venous thromboembolism (VTE), and reoperation. Results: A total of 12 patients underwent surgery with an average age of 75± 22 years. Indication for surgery included: 2 patients requiring fusion for severe primary osteoarthritis, 3 patients underwent primary arthrodesis following trauma and 7 patients underwent arthrodesis as a salvage procedure following failed primary fracture management. No patients had post-operative wound complications that required re-admission or a return to theatre, no VTE events, no fixation failures and 1 removal of screw for prominence. 6 patients have clinical and radiographic evidence of fusion, with the remaining 6 patients still under active follow-up and all still within 4 months of their fusion surgery. Conclusions: Our current experience suggests that arthrodesis is achievable with this novel minimally invasive approach, which is a safe and reproducible procedure without increase in operative complications.